Interrupted time series analysis on first cardiovascular disease hospitalization for adherence to lipid‐lowering therapy. Issue 2 (1st December 2019) - Hu, Feiyu; Warren, Jim; Exeter, Daniel J.
Abstract: Purpose: We analysed lipid‐lowering medication adherence before and after the first hospitalization for cardiovascular disease (CVD) to explore the influence hospitalization has on patient medication adherence. Methods: We extracted a sub‐cohort for analysis from 313, 207 patients who had primary CVD risk assessment. Adherence was assessed as proportion of days covered (PDC) ≥ 80% based on community dispensing records. Adherence in the 4 quarters (360 days) before the first CVD hospitalization and 8 quarters (720 days) after hospital discharge was assessed for each individual in the sub‐cohort. An interrupted time series design using generalized estimating equations was applied to compare the differences of population‐level medication adherence rates before and after the first CVD hospitalization. Results: Overall, a significant improvement in medication adherence rate from before to after the hospitalization was observed (odds ratio (OR) 2.49 [1.74‐3.57]) among the 946 patients included in the analysis. Patients having diabetes history had a higher OR of adherence before the hospitalization than patients without diabetes (1.50 [1.03‐2.22]) but no significant difference after the hospitalization (OR 1.13 [0.89‐1.43]). Before the first hospitalization, we observed that quarterly medication adherence rate was steady at around 55% (OR 0.97 [0.93‐1.01), whereas the trend in adherence over the post‐hospitalization period decreased significantly per quarter (OR 0.97 [0.94‐0.99]). Conclusions: Patients were more likely to adhere to lipid‐lowering therapy after experiencing a first CVD hospitalization. The change in medication adherence rate is consistent with patients having heightened perception of disease severity following the hospitalization.